21st Century Competencies (4C) on Improving Students' Social Skills - Rahmatiani, Lusiana; Darmawan, Cecep; Komalasari, Kokom; Rahmat (Universitas Pendidikan Ganesha, 2024)
The main challenge of education is to require students to have social skills. However, there are still many students who need more social skills. Students who lack social skills will feel challenged or have more difficulty adapting to the school environment. Based on this, this study aims to analyze 21st-century competencies (4C) to improve students' social skills. The method used in this study is a survey research method with a quantitative approach. This study uses a quasi-experiment with a one-group pretest posttest design. The population of this study was 423 class students. The sample of this study was 166 students. The methods of collecting data used were questionnaires, observations, and interviews. The instrument used in collecting data was a questionnaire sheet. The technique used to analyze the data was inferential statistics. The study results positively influenced 21st-century competencies (4C) and students' social skills. The regression coefficient shows that 21st-century competencies (4C) positively affect students' social skills. It is concluded that 21st-century competencies (4C) can improve students' social skills. Students' social skills are becoming increasingly important in the digital era. Therefore, improving students' social skills with 21st-century competencies (4C) in the learning process is necessary.